A luta das indigenas pelo direito à cidade: uma análise centrada nos afetos - Busarello, Flávia Roberta (2022)
The present research is considered the final product of a longitudinal participant- action research carried out since 2016 with Xokleng/Laklãnõ indigenous womenwholive in the urban context of Blumenau, SC. Its objective is to continue to strengthenthe fight of indigenous women who live in the urban context of Blumenau andtoanalyze the affective procedural of the indigenous women ingenium who live insuchspace, highlighting the desire for commonality and the shame. This methodologywaschosen to follow the affective procedural of the researchers-participants, as well as tostrengthen the fight and resistance of those who live in a markedly white context, thusreflecting on the praxis developed over these years. As an instrument, interviews, photographs, several meetings around the cityandparticipation in official events were used, where the participants were able to expresstheir indigenous ingenium. The theoretical reference is socio-historical psychology, based on the reflections of Vygotsky and Spinoza, deepening the categoryof Spinozist ingenium, and weaving its contributions to Social Psychology. The researchshowed how the affective link between shame and modesty leads to the camouflage of the indigenous ingenium, and also acts as a defense technique for the strategic conatusto survive and transit in the city. In the existence of camouflage, the superpositionof Blumenau's ingenium over the indigenous is evidenced. In this movement, one of theparadoxes highlighted in the research is also observed: migrating to the city in searchof their natural right to survive with dignity (SPINOZA, TP) requires themtocamouflage themselves as white in order to remain in this place. It is fromthe analysisof the ingenium movement that we also observe the breakdown of the indigenouscommons. It was observed that fear, hope, longing for the commonality, desideriumand loneliness constitute affections that make up the affective plot of indigenouspeople who live in the city, composing an intense ethical-political suffering. It isconcluded that self-love and the feeling of commonality are the remedies to prevent this suffering from crystallizing, blocking the force of action against the affective plot woven by the perverse inclusion of the indigenous who lives in Blumenau. It is fromthe longitudinal research that the relevance and potency of the ethical-political praxisof social psychology is verified together with and with indigenous peoples who liveinthe urban context. When the research listened to the affections, it broke withthehistorical silencing of these peoples, showing a powerful ethical-political praxis of psychology